Post-Sectarian Sunni Theology in Indonesia: A Theo-philosophical Engagement with Muhammadiyah and Nahdlatul Ulama - Muniron, Muniron; Dodi, Limas; Astuti, Fidia; Jainudin, Jainudin (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This article proposes an inclusive theo-philosophical approach as a new paradigm for mitigating ideological conflicts among contemporary Islamic groups, with particular attention to Muhammadiyah and Nahdlatul Ulama. Drawing on the integration of revelation and reason articulated by Amin Abdullah, as well as the faith-centered orientation developed by Hassan Hanafi, the study argues that the theological differences between the two organizations are predominantly methodological rather than substantive. Empirical findings from Kediri indicate that theological dialogue grounded in inclusive ethical principles can foster concrete practices of reconciliation, strengthen social cohesion, and reduce the potential for polarization. Drawing on John Hick’s reflections on pluralism, the article develops a model of reconciliation grounded in epistemic humility, dialogical hermeneutics, and historical consciousness. The analysis demonstrates that theological harmonization is not only feasible within the Indonesian Sunni context but also offers a meaningful contribution to global post-sectarian discourse. Ultimately, the study underscores the significance of an inclusive theo-philosophical paradigm as a foundation for articulating a more adaptive, moderate, and responsive Islamic theology that corresponds to the complexities of modern society.